2010
DOI: 10.1159/000318224
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Caries-Like Lesions in vitro on the Root Surfaces of Human Teeth in Solutions Simulating Plaque Fluid

Abstract: Lesion formation on root surfaces of human posterior teeth was studied in acetate/lactate buffers with a background electrolyte composition based on plaque fluid analyses. Lesion depth after 28 days at 37°C was measured in relation to: the presence or absence of cementum; the concentration of undissociated buffer; the presence or absence of magnesium ions at plaque fluid concentration. Each factor was evaluated at several values of –log(ion activity product for hydroxyapatite): pIHA. Solutions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 62 publications
0
18
0
2
Order By: Relevance
“…However, when a channel is demineralized by their action and dentin is reached, the community changes significantly and is predominantly proteolytic, and the main environmental pressure has an osmotic nature. At this stage, the tissue has a mineralized component with a lower proportion of hydroxyapatite and a higher critical pH which was estimated to be as high as 6.7 [Hoppenbrouwers et al, 1987], although lower values in the range 5.22-5.66 have been reported by recent in vitro work in root surfaces of human teeth [Shellis, 2010]. In addition, pH values in dentin caries lesions appear to be variable [Hojo et al, 1994].…”
Section: A Microbial-succession Tissue-dependent Hypothesis Of Dentamentioning
confidence: 91%
“…However, when a channel is demineralized by their action and dentin is reached, the community changes significantly and is predominantly proteolytic, and the main environmental pressure has an osmotic nature. At this stage, the tissue has a mineralized component with a lower proportion of hydroxyapatite and a higher critical pH which was estimated to be as high as 6.7 [Hoppenbrouwers et al, 1987], although lower values in the range 5.22-5.66 have been reported by recent in vitro work in root surfaces of human teeth [Shellis, 2010]. In addition, pH values in dentin caries lesions appear to be variable [Hojo et al, 1994].…”
Section: A Microbial-succession Tissue-dependent Hypothesis Of Dentamentioning
confidence: 91%
“…The concentration of calcium and phosphate ions in saliva and dental plaque are important factors (Paschalis et al 1996). Some studies indicate that the concentration of magnesium (Mg) prohibits the dissolution of hydroxyapatite crystals (Paschalis et al 1996), while other studies claim that Mg is of no or minor importance (Shellis 2010). The pH-level when cementum starts to dissolve has been suggested to be as high as 6.7 (Hoppenbrouwers et al 1987), but this has been questioned by other researchers who have analysed the so called pI(HA) values (Shellis 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, comparatively few such studies were conducted on root caries lesions as researchers have generally focused on lesion creation under different conditions [Shellis, 2010;Moron et al, 2013] or the study of fluoride and/or potentially cariostatic agents on de-and remineralization of one particular lesion type in situ [Wefel et al, 1995[Wefel et al, , 2002 and in vitro [Xie et al, 2008;Qia et al, 2012]. Nonetheless, a series of mechanistic studies [Kawasaki et al, 2000;Smith et al, 2005;Preston et al, 2008] found that lesion baseline mineral distribution affects fluoride response under subsequent remineralization, that smaller lesions are more prone to remineralization and that, as shown for enamel [ten Cate and Duijsters, 1982], the mineral and fluoride content of the surface layer determines the rate of remineralization.…”
mentioning
confidence: 99%